Foodborne Outbreak Investigation in Elementary School Students in Bantul, Yogyakarta, 2023 - Soraya Isfandiary Iskandar; Miftakhul Janah; Samsu Aryanto; Bayu Satria Wiratama (Media Kesehatan Masyarakat Indonesia, 2024)
Bantul District Health Office received notification that 75 students in elementary school were sick with symptoms of nausea, vomiting, and dizziness after they consumed snacks from the school canteen. An epidemiological investigation was conducted to confirm the outbreak, identify additional cases, determine risk factors and causes, and recommend preventive measures. This investigation conducted active case finding followed by a retrospective cohort study. Individuals who experience one or more symptoms, such as nausea, vomiting, diarrhea, stomach pain, dizziness, fever, and malaise after consuming snacks were defined as cases. Data was collected through direct interviews with students, teachers, staff, and food sellers. Samples of food and vomit were collected and sent to the health laboratory. Data were analyzed using chi-square and multiple binomial regression. There were 150 cases. Most cases were found in the female group (53.22%), 9-year-old group (55.32%), and third-grade students (65%). Dizziness (66.67%), vomiting (56.67%), and nausea (46%) were the most common symptoms. The epidemic curve was a common source, with incubation periods ranging from one to 26 hours. Meatballs were associated with the increased risk of becoming a case in this outbreak (aRR = 1.49; 95% CI = 1.22-1.81). The causative agent was suspected to be Salmonella spp, but the laboratory analysis results were inconclusive due to contamination. Potential risk factors were large storage in the refrigerator, insufficient reheating, and cross-contamination. Improvements in food safety monitoring for schools and food handlers, along with appropriate sampling by healthcare facilities, are required to control outbreaks.